Cholesterol lowering effect in the gall bladder of dogs by a standardized infusion of Herniaria hirsuta L. (1st July 2015) - van Dooren, Ines; Faouzi, My El Abbes; Foubert, Kenn; Theunis, Mart; Pieters, Luc; Cherrah, Yahya; Apers, Sandra
Abstract: Etnopharmacological relevance: Infusions of Herniaria hirsuta L., Herniaria glabra L. and Herniaria fontanesii J.Gay are well known in Moroccon folk medicine for the treatment of biliary dyskinesia, (uro)lithiasis or as a diuretic. Herniariae Herba which can contain H. glabra and H. hirsuta is known in Europe as an urological drug. Aim of the study: To investigate the efficacy of a standardized infusion of Herniaria hirsuta against choleltihiasis, and evaluation of its genotoxicity. Methods and materials: An analytical HPLC-UV method to quantify flavonoids and saponins present in the extract of H. hirsuta was developed and validated. An in vivo experiment to evaluate the cholesterol lowering effect of a infusion of H. hirsuta in the gall bladder of dogs was carried out. Dogs were divided into 3 groups i.e. control dogs (CG), dogs treated with ursodeoxycholic acid (UDCA) (2×7.35 mg/kg body weight/day) and dogs treated with the standardized infusion (HG) (2×48.5 mg/kg body weight/day). Dogs were fed a fatty diet during 120 days after which a diet without additional fat was introduced till day 180. Treatment started 30 days after introduction of the fatty diet and lasted till the end of the experiment. A bile and blood sample of each dog was collected every 30 days, after which the concentration of cholesterol was determined. An Ames test was performed according to the OECD-guidelines. Results: The validated HPLC-UV method showed a linear calibration model and an acceptable precision for the total flavonoid content (total content 4.51%) as well as the total saponin content (12.74%). The in vivo experiments already showed a minor difference for bile cholesterol between CG and HG after 30 days of treatment with the infusion, and the difference was more pronounced after 90 days of treatment. Even 30 days after discontinuation of the cholesterol-rich diet a significant difference remained between CG and HG. There was no statistically significant difference in blood cholesterol. The Ames test showed that the infusion of H. hirsuta could be considered as being free from genotoxic risks. Conclusion: A method for the standardization of a infusion of Herniaria hirsuta was developed and validated. Prolonged use of this standardized H. hirsuta extract resulted in a cholesterol-lowering effect in the bile of dogs. Since this pharmacological effect prevents the formation of gallstones and can contribute to solving existing gallstones, a standardized infusion of H. hirsuta may have a positive effect in the treatment of gallstones in human patients. Graphical abstract: